Towards the development of an electrochemical aptasensor for the early detection of ovarian cancer using the novel biomarker HSP10 and aptamer bioreceptors - Maharaj, Tarushai (Stellenbosch : Stellenbosch University, 2025)
Thesis (MEngSci)--Stellenbosch University, 2025.